2015
DOI: 10.1152/jn.01010.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cell dialysis by sharp electrodes can cause nonphysiological changes in neuron properties

Abstract: Cell dialysis by sharp electrodes can cause nonphysiological changes in neuron properties. J Neurophysiol 114: 1255-1271, 2015. First published June 10, 2015 doi:10.1152/jn.01010.2014.-We recorded from lobster and leech neurons with two sharp electrodes filled with solutions often used with these preparations (lobster: 0.6 M K 2 SO 4 or 2.5 M KAc; leech: 4 M KAc), with solutions approximately matching neuron cytoplasm ion concentrations, and with 6.5 M KAc (lobster, leech) and 0.6 M KAc (lobster). We measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 28 publications
4
36
0
Order By: Relevance
“…As has been observed previously (Hooper et al 2015), in the PD neurons the current necessary to achieve 0 mV showed a large decrease during the 10 depolarizing steps ( Fig. 2A).…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…As has been observed previously (Hooper et al 2015), in the PD neurons the current necessary to achieve 0 mV showed a large decrease during the 10 depolarizing steps ( Fig. 2A).…”
Section: Methodssupporting
confidence: 84%
“…We therefore filled the microelectrodes with solutions whose ion concentration matched the cytoplasmic ion concentration of the neuron type being recorded from: for lobster (in mM), 20 NaCl, 15 Na 2 SO 4 , 400 K-gluconate, 10 MgCl 2 , and 10 HEPES, pH 7.2; for leech (in mM), 7.6 NaCl, 1.4 Na 2 SO 4 , 112 K-gluconate, 0.2 MgCl 2 , and 10 HEPES, pH 7.2. When recorded from with electrodes filled with these solutions, outward current amplitudes are stable for the entire recording times used in the experiments reported here (Hooper et al 2015).…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…Intracellular recordings from somata were performed in the desheathed STG with 10-30 MΩ sharp glass microelectrodes filled with internal solution (10 mM MgCl2, 400 mM potassium gluconate, 10 mM HEPES buffer, 15 mM NaSO4, 20 mM NaCl as in (Hooper et al, 2015). Intracellular signals were amplified with an Axoclamp 900A amplifier (Molecular Devices).…”
Section: Electrophysiologymentioning
confidence: 99%
“…The STG was desheathed for access to somata for intracellular recordings. These recordings were executed with glass micropipettes (20-30 MΩ) filled with internal solution: 10 mM MgCl2, 400 mM potassium gluconate, 10 mM HEPES buffer, 15 mM NaSO4, 20 mM NaCl (Hooper et al, 2015). Intracellular recordings signals were amplified with an Axoclamp 900A amplifier (Molecular Devices, as described in Otopalik et al 2017b).…”
Section: Electrophysiology and Dye-fillsmentioning
confidence: 99%